Integrated Quality Management and a Critical Review of Its Application in Educational Institutions - Muhammad Faqih Nidzom; Dwi Setyo Pambudi; Risqi Albana Mahmud (At-Ta'dib, 2022)
This study aims to delve deeper into the management commonly used by educational institutions. The management of educational institutions adopts control in industry and business, with some adjustments to meet the needs of stakeholders, so that the success of educational institutions is determined by stakeholder satisfaction. It is not wrong if educational institutions implement integrated quality management. Still, suppose, it is not carefully mixed and filtered. In that case, this kind of management becomes a significant factor in changing educational goals, measuring the progress of educational institutions, and damaging teacher-student relationships in the world of education. At the end of the study, there are several points in Islamic education to filter the values that must be maintained in the implementation of quality management of educational institutions and maintain educational goals, measures of the progress of educational institutions, and the relationship that should exist between teachers and students.